Detection of Oxytetracycline in Citrus Phloem and Xylem Saps Using Europium-Based Method - Faraj Hijaz; Yasser Nehela; Ozgur Batuman; Nabil Killiny (MDPI AG, 2021)
Oxytetracycline (OTC) has been used for the control of several plant diseases and was recently approved for the control of Huanglongbing, the citrus greening disease. Huanglongbing is caused by the phloem limited 'Candidatus Liberibacter asiaticus'. Determination of OTC in the xylem and phloem of citrus plants is of great interest as they are the main routes of translocation in citrus. In addition, the determination of the level of OTC in the phloem sap is necessary for the control of the 'Ca. L. asiaticus' pathogen, which resides in the phloem. Herein, we demonstrated that the level of OTC in the citrus phloem and xylem saps obtained using the centrifugation method can be successfully measured using the europium (Eu) method directly or with cleanup by solid-phase extraction (SPE). Recovery of OTC from spiked sap samples purified by solid-phase extraction (SPE) was higher than 90%, while recovery from saps without SPE cleanup were nearly 100%. The 'Ca. L. asiaticus'-infected leaf and phloem sap samples showed higher inhibition of the fluorescence intensity of the OTC standard compared to non-infected control leaf and phloem samples. In agreement with this finding, the levels of phenols and flavonoids in 'Ca. L. asiaticus'-infected leaves were higher than those controls and were shown to interfere with the Eu method. Therefore, the SPE cleanup step only improved OTC recovery from leaf samples containing the interfering compounds. The Eu method was then used to determine OTC levels in the phloem and xylem sap of OTC-treated plants, and the results were similar whether measured directly or after SPE. Visualization under ultraviolet light (400 nm) showed the presence of OTC in citrus xylem and phloem saps with and without the use of SPE.